Nitrous oxide and nitric oxide fluxes differ from tea plantation and tropical forest soils after nitrogen addition - Toteva, Galina Y.; Reay, David; Jones, Matthew R.; Cowan, Nicholas; Deshpande, Ajinkya; Weerakoon, Buddhika; Nissanka, Sarath; Drewer, Julia (Frontiers in Forests and Global Change, 2024)
South Asia is experiencing a rapid increase in nitrogen (N) pollution which is predicted to continue in the future. One of the possible implications is an increase in gaseous reactive N losses from soil, notably in the form of nitrous oxide (N2O) and nitric oxide (NO). Current knowledge of N2O and NO dynamics in forest ecosystems is not sufficient to understand and mitigate the impacts on climate and air quality. In order to improve the understanding of emissions from two major land uses in Sri Lanka, we investigated the emission potential for N2O and NO fluxes measured by absorption spectroscopy and chemiluminescence, respectively, in response to three different N addition levels (the equivalent of 0, 40 and 100 kg N ha -1 yr -1 deposition in the form of NH4 + ) from soils of two typical land uses in Sri Lanka: a secondary montane tropical forest and a tea plantation using soil laboratory incubations of repacked soil cores. We observed an increase in NO fluxes which was directly proportional to the amount of N applied in line with initial expectations (maximum flux ranging from 6 -8 ng NO-N g -1 d -1 and from 16 -68 ng NO-N g -1 d -1 in forest and tea plantation soils, respectively). However, fluxes of N2O did not show a clear response to N addition, the highest treatment (100N) did not result in the highest fluxes. Moreover, fluxes of N2O were higher following the addition of a source of carbon (in the form of glucose) across treatment levels and both land uses (maximum flux of 2 -34 ng N2O-N g - 1 d -1 in forest and 808 -3,939 ng N2O-N g -1 d -1 in tea plantation soils). Both N2O and NO fluxes were higher from tea plantation soils compared to forest soils irrespective of treatment level, thus highlighting the importance of land use and land management for gaseous reactive N fluxes and therefore N dynamics.